Early Descriptions of Family Caregivers' Experiences With Unexpected Lucidity. (17th December 2021) - Kim, Kyungmin; Griffin, Joan; Bangerter, Lauren; Biggar, Virginia; Finnie, Dawn; Frangiosa, Theresa; Gaugler, Joseph; Lapid, Maria
Abstract: To develop an operational definition of and typologies for episodes of lucidity (EL), we conducted a cross-sectional study of former/current family caregivers from UsAgainstAlzheimer's A_LIST (N = 538). More than 60% of caregivers (n = 294, 62%) reported witnessing EL with their care recipient over the course of their dementia. Most episodes happened in late stages of dementia (71%). Only 10% happened within 7 days before death. The majority of episodes (71%) lasted <30 minutes. About half the episodes were characterized by uncharacteristic speech and communication. Caregivers perceived these experiences positively (M = 4.10; range = 1–5), but also expressed desire to know why/when EL occurs and how to best respond to it. Data will be used to refine definitions and typologies, and then a prospective, demographically diverse survey will be administered to family caregivers to assess predictors of EL, linking EL to caregiver well-being and bereavement response.